Socioeconomic Dynamics and Poverty Rate in East Java: A Panel Regression Investigation - Sa'diyah, Nabilah; Pimada, Laila M. (Journal of Developing Economies, 2024)
Economic development can be described as a process of system or non-social system in order to achieve a better condition. It is often related to public welfare as evidenced by the poverty phenomenon experienced by the population. The population growth in a country must be controlled in order to prevent a threat to the country's welfare, since an increase in the population will lead to an increase in the need for fulfillment. This condition should be balanced with a proper income alignment. East Java Province has the second highest population in Indonesia. In fact, this condition has had an impact on the economic development process, particularly in East Java, where there has been an increase in the poverty rate. Over the past decade, the poverty rate in East Java has fluctuated. It showed an increase in a few years, namely 2015, 2020, and 2021, with an average increase of 0.88%. This study aims to identify the effects of several factors on the poverty rate in East Java between 2017 and 2022. Furthermore, this study used a quantitative method with a panel regression analysis. The independent variables included open unemployment rate, labor force participation rate, minimum wage, and education level. This study found that open unemployment rate and minimum wage affected poverty rate. In contrast, labor force participation rate and education level did not affect poverty rate.